A survey of mobile database security threats and solutions for it - Ghorbanzadeh, P; Shaddeli, A; Malekzadeh, R; Jahanbakhsh, Z (2010 3rd International Conference on Information Sciences and Interaction Sciences, 2010)
This article show different mobile database security threats that may be occurs for mobile database in the real world and gives possible solution to eliminate them. Mobile database is a specialized class of distributed systems. There are security challenges due to the distributed nature of the mobile database application and the hardware constraints of mobile devices. In this document, we will deals with the subject of security in four fields. These four areas include: Security of mobile device, security of operating system on mobile device, security of mobile database and security of mobile network. We identify a set of security vulnerabilities on mobile database and try to apply appropriate technique to decrease side affect for mobile database security. Important security issues for mobile device, mobile operating system and mobile network that maybe affect on mobile database security are discussed along with possible solution. Finally, for more security, this paper offers a comprehensive solution that may be applied to distributed database.